Validation of Work Need Satisfaction Scales Among Chinese Working Adults: A Psychology of Working Theory Perspective. (February 2022) - Xu, Yan; Li, Chaoping; Wang, Jiayan; Lan, Yuanmei
This study translated the Work Need Satisfaction Scales (WNSS), which was conceptualized in the Psychology of Working Theory (PWT), and tested the reliability and validity of the Chinese version (WNSS-C). In Study 1 ( N = 423), the WNSS was translated into Chinese, and an exploratory factor analysis yielded a five-factor solution representing needs related to survival, social contribution, competence, relatedness, and autonomy. In Study 2 ( N = 425), confirmatory factor analyses found no significant differences between the correlated five-factor, higher-order, and higher-order self-determination needs models. The results suggest the effectiveness of using a flexible five-factor model. Then, configural, metric, and scalar invariance models were tested, demonstrating that the WNSS-C is equivalent across gender, age, education level, and job position. Finally, we tested the concurrent, convergent, and discriminant validity of the WNSS-C and demonstrated that WNSS-C is a useful tool in the Chinese context.